given the system express y as a function of t
Given the system let us express "y" as a function of "t." Let us add to "3\\frac{dx}{dt}+2\\frac{dy}{dt}-x+y=t-1" the equation "\\frac{dx}{dt}+\\frac{dy}{dt}-x=t+2" multiplied by "-3." We have that "-\\frac{dy}{dt}+2x+y=-2t-7." It follows that "x=\\frac{1}{2}\\frac{dy}{dt}-\\frac{1}{2}y-t-\\frac{7}{2}," and hence "\\frac{dx}{dt}=\\frac{1}{2}\\frac{d^2y}{dt^2}-\\frac{1}{2}\\frac{dy}{dt}-1." We get the equation "\\frac{1}{2}\\frac{d^2y}{dt^2}-\\frac{1}{2}\\frac{dy}{dt}-1+\\frac{dy}{dt}-(\\frac{1}{2}\\frac{dy}{dt}-\\frac{1}{2}y-t-\\frac{7}{2})=t+2" which is equivalent to "\\frac{1}{2}\\frac{d^2y}{dt^2}+\\frac{1}{2}y=-\\frac{1}{2}," and hence to "\\frac{d^2y}{dt^2}+y=-1." The characteristic equation "k^2+1=0" have the roots "k_1=i" and "k_2=-i." It follows that the solution is of the form "y(t)=C_1\\cos t+C_2\\sin t+y_p," where "y_p=a." It follows that "\\frac{d^2y_p}{dt^2}=0," and hence "a=-1." Therefore, the solution is the following:
"y(t)=C_1\\cos t+C_2\\sin t-1."
Comments
Leave a comment